Incomplete Inhibition of Platelet Aggregation and Glycoprotein IIb-IIIa Receptor Blockade by Abciximab: Importance of Internal Pool of Glycoprotein IIb-IIIa Receptors - Gawaz, Meinrad; Ruf, Andreas; Pogatsa-Murray, Gisela; Dickfeld, Timm; Rüdiger, Silja; Taubitz, Winfried; Fischer, Jörg; Müller, Iris; Meier, Dieter; Patscheke, Heinrich; Schömig, Albert (Thrombosis and Haemostasis, 2000)
Resting platelets contain a substantial internal pool of GPIIb-IIIa complexes that is exposed on the surface of activated platelets. Whether the exposure of internal GPIIb-IIIa complexes on the activated platelet surface affects therapy with GPIIb-IIIa antagonists is poorly understood. We addressed this issue in thirteen patients who underwent elective coronary stenting and received abciximab. Platelet aggregation, surface expression of GPIIb-IIIa and P-selectin, receptor blockade of GPIIb-IIIa, and platelet release in response to ADP and thrombin-receptor activating peptide (TRAP) were determined ex vivo by Lumi-aggregometry and flow cytometry before, during and after abciximab administration. We found that inhibition of aggregation and GPIIb-IIIa blockade of ADP-stimulated platelets was almost complete during abciximab administration. In contrast, when TRAP was used to stimulate platelets ex vivo aggregation was only partially inhibited, most likely due to release of internal pool of unblocked GPIIb-IIIa complexes. Using electron microscopy we found that 7E3-occupied GPIIb-IIIa complexes are internalized into the surface connected system (SCS) and the α-granules of washed platelets which was associated with a reduced degranulation of the α-granula membrane protein P-selectin. We conclude, that despite internalization of abciximab into the internal pool of GPIIb-IIIa, upon strong platelet activation with thrombin a significant amount of unblocked internal GPIIb-IIIa can be exposed on the platelet surface and mediate platelet aggregation. Incomplete blockade of the internal GPIIb-IIIa pool may limit clinical efficacy of abciximab.
Keywords: Platelets; GPIIb-IIIa; abciximab; internal pool; GPIIb-IIIa inhibitors